Database development of Islamic information credibility system / Norain Ahmad - Ahmad, Norain (2014)
Islamic Information Credibility System (IICS) was developed for those who want to know or check on the credibility of Islamic information they gather through Internet such as articles, forum and other sources which the people believe that Islamic information they gather from the Internet are credible without any hesitation and because there is no such system to checking on the credibility of the information itself. Therefore, the system was developed and the goals of the development of the system are to check the credibility contents of Islamic information especially on the solah information. To store all information about solah a database is design by using MySQL Workbench. Before the database is design the table required to store the keyword is identify and later come out with the entity relationship diagram with their relationship. From the entity relationship diagram (ERD), the SQL command is generated and ready for importing to Java DB database in the NetBeans IDE 7.1. Then, the system automatically calculates for them the percentage how much credible solah information they paste on the system. In the conclusion, the system successfully run to checking on the solah information and user can know how much credible the solah information they insert by getting the percentage at last. The percentage show how credible those information, if the percentage higher more credible the information but inverse if the percentage lower.